Utilization of Web-Facilitated Learning to Improve Teacher Skills in Identifying Basic Competencies - Moh. Rifqi Rahman; Bina Prima Panggayuh; Evi Fatimatur Rusydiyah (Yayasan Keluarga Guru Mandiri, 2022)
The use of technology has the potential to build more intensive learning and make it easier for teachers to carry out student learning assessments. The present study was aimed to analyze the extent of the benefits of web-facilitated learning as a form of technology product to grow teacher skills incorrectly identifying basic competencies. This study surveyed the activities of the Islamic Religious Education Teacher Working Group (KKG) in Surabaya and analyzes it using the Miles and Huberman model. The results showed that the use of web-based facilitated learning in this study is quite effective. This was based on five main factors, namely usability 83%, usefulness of content 86%, adequacy of information 87%, accessibility 82%, and interaction 81%. The total average score was 83% and shows very good quality. Several issues regarding the barriers to implementation were discussed.